Investigation of thermal adaptation and development of an adaptive model under various cooling temperature settings for students’ activity rooms in a university building in malaysia - Nurul, Izzati; Sheikh Ahmad, Zaki; Rijal, Hom Bahadur; Rey, Jorge Alfredo Ardila; Hagishima, Aya; Nurizzatul Atikha, Rahmat (MDPI, 2023)
The use of an air conditioner (AC) becomes essential, particularly in a hot and humid climate, to provide a comfortable environment for human activities. The setpoint is the agreed temperature that the building will meet, and the use of the lowest setpoint temperature to accelerate the cooling of indoor spaces should be avoided. A comprehensive field study was conducted under various cooling temperature settings in two student activity rooms in a university building in Malaysia, so as to understand respondents’ characteristics and behavior toward AC usage, to estimate the comfort at various indoor temperatures, to develop an adaptive model of thermal comfort in AC spaces, and to compare the comfort temperature with related local and international indoor thermal environmental standards. The findings indicated that water intake and clothing insulation affected personal thermal comfort. Moreover, the mean comfort temperature for respondents was 24.3 °C, which is within an indoor thermal comfort zone of 23–27 °C. The findings suggest that the preference of occupants living in a hot and humid region for lower temperatures means that setting temperatures lower than 24 °C might underestimate the indoor comfort temperature. Additionally, an adaptive relationship can be derived to estimate the indoor comfort temperature from the prevailing outdoor temperature.